Systematic Review and Future Research Directions on Privacy Preservation Techniques Using Blockchain - Sandip S. Chauhan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Big data is an extremely large data set with a diverse and complicated production of organized and unstructured data. The management of storing, analyzing, and finding meaningful outcomes from processing data is usually aided by the characteristics of big data Through its decentralized system architecture, block chain technology ensures data protection and privacy. Due to the block chain consensus process and encryption, data recorded in the block chain is tempered proof and cannot be readily changed, and a massive amount of computing power will be necessary. Through its connected chain, block chain’s transaction ledger offers data auditing. Data auditing is possible thanks to block chain’s transaction ledger. All valid data transfers are recorded and put into the block chain ledger, which assures data quality through a variety of verification processes. Block chain is also used in the big data mining process, where data is collected from many networks and organizations with the purpose of demonstrating data with an exponential growth in risk factors. A block chain platform can also assist data scientists in monetizing their labour by allowing them to trade analytic results stored on the network.